MIOCENE STRATIGRAPHY AND GEOLOGICAL HISTORY OF THE CRIMEAN PLAIN REGION - Barg I.M.; Ivanova T.A. (My University, 2000)
Local Miocene Stratigraphic Schemes for different plain areas in the Crimea are substantiated and correlated with the Crimea-Caucasus regional scale validated in adjacent territories. New data are used to elucidate the Miocene geological history of the Crimean Plain.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен